Neutrophil Extracellular Traps Induce the Epithelial-Mesenchymal Transition: Implications in Post-COVID-19 Fibrosis - Pandolfi, Laura (Front Immunol, 2021)
The release of neutrophil extracellular traps (NETs), a process termed NETosis, avoids pathogen spread but may cause tissue injury. NETs have been found in severe COVID-19 patients, but their role in disease development is still unknown. The aim of this study is to assess the capacity of NETs to drive epithelial-mesenchymal transition (EMT) of lung epithelial cells and to analyze the involvement of NETs in COVID-19. Bronchoalveolar lavage fluid of severe COVID-19 patients showed high concentration of NETs that correlates with neutrophils count; moreover, the analysis of lung tissues of COVID-19 deceased patients showed a subset of alveolar reactive pneumocytes with a co-expression of epithelial marker and a mesenchymal marker, confirming the induction of EMT mechanism after severe SARS-CoV2 infection. By airway in vitro models, cultivating A549 or 16HBE at air-liquid interface, adding alveolar macrophages (AM), neutrophils and SARS-CoV2, we demonstrated that to trigger a complete EMT expression pattern are necessary the induction of NETosis by SARS-CoV2 and the secretion of AM factors (TGF-β, IL8 and IL1β). All our results highlight the possible mechanism that can induce lung fibrosis after SARS-CoV2 infection.